Macrophages regulate vascular smooth muscle cell function during atherosclerosis progression through IL-1β/STAT3 signaling - Xue, Yuzhou; Luo, Minghao; Hu, Xiankang; Li, Xiang; Shen, Jian; Zhu, Wenyan; Huang, Longxiang; Hu, Yu; Guo, Yongzheng; Liu, Lin; Wang, Lingbang; Luo, Suxin (Communications biology, 2022)
Vascular smooth muscle cells (VSMCs) play a central role in atherosclerosis progression, but the functional changes in VSMCs and the associated cellular crosstalk during atherosclerosis progression remain unknown. Here we show that scRNA-seq analysis of proximal adjacent (PA) and atherosclerotic core (AC) regions of human carotid artery plaques identifies functional alterations in macrophage-like VSMCs, elucidating the main state differences between PA and AC VSMCs. And, IL-1β mediates macrophage-macrophage-like VSMC crosstalk through regulating key transcription factors involved in macrophage-like VSMCs functional alterations during atherosclerosis progression. In vitro assays reveal VSMCs trans-differentiated into a macrophage-like phenotype and then functional alterations in response to macrophage-derived stimuli. IL-1β promots the adhesion, inflammation, and apoptosis of macrophage-like VSMCs in a STAT3 dependent manner. The current findings provide interesting insight into the macrophages-macrophage-like VSMC crosstalk, which would drive functional alterations in the latter cell type through IL-1β/STAT3 axis during atherosclerosis progression. Characterisation of macrophages from human carotid artery plaques and in vitro assays reveal that macrophages regulate vascular smooth muscle cell function during atherosclerosis progression through the IL-1β/STAT3 axis.